HBV Reactivation During the Treatment of Non-Hodgkin Lymphoma and Management Strategies - Cao, Xing; Wang, Yafei; Li, Panyun; Huang, Wei; Lu, Xiaojuan; Lu, Hongda (Frontiers in Oncology, 2021)
Hepatitis B virus reactivation (HBV-R), which can lead to HBV-related morbidity and mortality, is a common and well-known complication that occurs during the treatment of non-Hodgkin lymphoma (NHL) patients with current or past exposure to HBV infection. HBV-R is thought to be closely associated with chemotherapeutic or immunosuppressive therapies. However, immunosuppressive agents such as anti-CD20 antibodies (e.g., rituximab and ofatumumab), glucocorticoids, and hematopoietic stem cell transplantation (HSCT) administered to NHL patients during treatment can cause deep immunodepression and place them at high risk of HBV-R. In this review, we explore the current evidence, the guidelines of several national and international organizations, and the recommendations of expert panels relating to the definition, risk factors, screening and monitoring strategies, whether to use prophylaxis or pre-emptive therapy, and the optimal antiviral agent and duration of antiviral therapy for HBV-R.